Design, methodology, and baseline of eastern China student health and wellbeing cohort study - Xiyan Zhang; Xiyan Zhang; Genming Zhao; Jun Ma; Fangbiao Tao; Chen-Wei Pan; Fengyun Zhang; Yan Wang; Wenyi Yang; Yao Xiang; Xin Wang; Yunfan Tian; et al. (Frontiers Media S.A., 2023)
PurposeTo describe the study design, methodology, and cohort profile of the Eastern China Student Health and Wellbeing Cohort Study. The cohort baseline includes (1) targeted disease (myopia, obesity, elevated blood pressure, and mental health) and (2) exposures (individual behaviors, environment, metabolomics, and gene and epigenetics).ParticipantsAnnual physical examination, questionnaire-based survey, and bio-sampling have been carried out in the study population. In the first stage (2019-2021), a total of 6,506 students in primary schools are enrolled in the cohort study.Findings to dateOf all the cohort participants, the ratio of male to female is 1.16 among a total of 6,506 student participants, of which 2,728 (41.9%) students are from developed regions and 3,778 (58.1%) students are from developing regions. The initial age of observation is 6-10 years, and they will be observed until they graduate from high school (>18 years of age). (1) Targeted diseases: The growth rates of myopia, obesity, and high blood pressure vary by regions, and for developed regions, the prevalence of myopia, obesity, and elevated blood pressure is 29.2%, 17.4%, and 12.6% in the first year, respectively. For developing regions, the prevalence of myopia, obesity, and elevated blood pressure is 22.3%, 20.7%, and 17.1% in the first year, respectively. The average score of CES-D is 12.9 ± 9.8 in developing regions/11.6 ± 9.0 in developed regions. (2) Exposures: ① The first aspect of individual behaviors: the questionnaire topics include diet, physical exercise, bullying, and family. ② The second aspect of environment and metabolomics: the average desk illumination is 430.78 (355.84-611.56) LX, and the average blackboard illumination is 365.33 (286.83-516.84) LX. Metabolomics like bisphenol A in the urine is 0.734 ng/ml. ③ The third aspect of gene and epigenetics: SNPs (rs524952, rs524952, rs2969180, rs2908972, rs10880855, rs1939008, rs9928731, rs72621438, rs9939609, rs8050136 and so on) are detected.Future plansEastern China Student Health and Wellbeing Cohort Study is aiming to focus on the development of student-targeted diseases. For children with student common diseases, this study will focus on targeted disease-related indicators. For children without targeted disease, this study aims to explore the longitudinal relationship between exposure factors and outcomes, excluding baseline confounding factors. Exposure factors include three aspects: (1) individual behaviors, (2) environment and metabolomics, and (3) gene and epigenetics. The cohort study will continue until 2035.